Clinical investigation of esophageal injury from cryoballoon ablation of persistent atrial fibrillation. Issue 2 (2nd January 2019) - Shigeta, Takatoshi; Okishige, Kaoru; Aoyagi, Hideshi; Nishimura, Takuro; Nakamura, Rena A.; Ito, Naruhiko; Tsuchiya, Yusuke; Asano, Mitsutoshi; Shimura, Tsukasa; Suzuki, Hidetoshi; Kurabayashi, Manabu; Fukami, Yuichi; et al.
Abstract: Background: The cryoballoon (CB) can be utilized for extra pulmonary vein (PV) ablation such as for a left atrial (LA) posterior wall (LAPW) isolation. However, scrutiny of the esophageal injuries during the LAPW isolation has never been performed. We sought to thoroughly investigate the esophageal lesions (ELs) and gastric hypomotility (GH) caused by an LAPW isolation using a CB. Methods: A total of 101 persistent atrial fibrillation patients who underwent an LAPW isolation using a CB were enrolled. The CB was applied on the roof and bottom area of the LAPW after a PV isolation. The luminal esophageal temperature (LET) was monitored by a thermistor probe during the CB applications. When the LET reached 15°C, the freezing application was prematurely interrupted. Esophagogastroscopy was performed on the next day following the ablation. Results: All PVs were successfully isolated in all patients. A successful LAPW isolation solely with CB ablation was performed in 72 (71.3%) patients. Cryofreezing applications were prematurely interrupted due to low LETs in 49 (48.5%) patients predominantly during the LA bottom line ablation. ELs and GH were observed in 11 (10.9%) and 16 patients (15.8%), respectively. The nadir LET tended to be lower in patients with ELs and GH than in those without (ELs: 14.8 ± 4.5°C vs 17.4 ± 6.0°C, P = 0.17; GH: 15.5 ± 4.5°C vs 17.5 ± 6.1°C, P = 0.23, respectively). Conclusions: Esophageal complications such as ELs and GH occur during the LAPW isolation with a CB. There was no reliable predictor of those adverse events.